2016
DOI: 10.5194/tc-10-1883-2016
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and variability of ice-stream grounding lines on retrograde bed slopes

Abstract: Abstract. In many ice streams, basal resistance varies in space and time due to the dynamically evolving properties of subglacial till. These variations can cause internally generated oscillations in ice-stream flow. However, the potential for such variations in basal properties is not considered by conventional theories of grounding-line stability on retrograde bed slopes, which assume that bed properties are static in time. Using a flow-line model, we show how internally generated, transient variations in ic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 65 publications
(86 reference statements)
3
27
0
Order By: Relevance
“…Thus, we refer to studies designed to model this ice sheet when it comes to the proper representation of the characteristic surge frequency of Heinrich events (e.g., Marshall and Clarke, 1997;Calov et al, 2002;Papa et al, 2006;Roberts et al, 2016). Our model results are closer to results from conceptual studies which also use an idealized geometry (e.g., Bougamont et al, 2011;Van Pelt and Oerlemans, 2012;Robel et al, 2016). These studies all yield a surgecycle duration of ∼ 1000-2000 years despite considerable differences in degree of physical approximations, parameterizations and complexity in setup geometry.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Thus, we refer to studies designed to model this ice sheet when it comes to the proper representation of the characteristic surge frequency of Heinrich events (e.g., Marshall and Clarke, 1997;Calov et al, 2002;Papa et al, 2006;Roberts et al, 2016). Our model results are closer to results from conceptual studies which also use an idealized geometry (e.g., Bougamont et al, 2011;Van Pelt and Oerlemans, 2012;Robel et al, 2016). These studies all yield a surgecycle duration of ∼ 1000-2000 years despite considerable differences in degree of physical approximations, parameterizations and complexity in setup geometry.…”
Section: Discussionsupporting
confidence: 66%
“…Numerical modeling studies that investigated ice-sheet-intrinsic surging include the demon-stration of creep instability (Clarke et al, 1977) and hydraulic runaway (Fowler and Johnson, 1995) as possible main feedbacks that drive unforced surging, the application to the Laurentide Ice Sheet to simulate its quasi-periodic surging (Marshall and Clarke, 1997;Calov et al, 2002Calov et al, , 2010Greve et al, 2006;Papa et al, 2006;Roberts et al, 2016), the simulation of (cyclic) ice streaming and stagnation reminiscent of the flow variability of the Siple Coast ice streams (Alley, 1990;Pattyn, 1996;Payne and Dongelmans, 1997;Fowler and Schiavi, 1998;Bougamont et al, 2011;Van Pelt and Oerlemans, 2012;Robel et al, 2013) and the investigation of ice-stream oscillations in interaction with bed topography under the influence of ice-shelf buttressing (Robel et al, 2016). Model complexity ranges from the consideration of a simple slab of ice (e.g., Clarke et al, 1977) to the solution of the full Stokes equations to simulate real-world problems using satellite data (Kleiner and Humbert, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These include the appearance of "hoop stresses" in an ice shelf fringing the ice sheet (see Pegler andWorster, 2012, andPegler, 2016, though these may require unrealistically large ice shelves), the fact that bedrock elevation can actually change due to loading and unloading of the lithosphere (Gomez et al, 2010), thermomechanically mediated changes in basal friction (Robel et al, 2014(Robel et al, , 2016 and lateral drag due to geometrical confinement of the flow into a channel (Dupont and Alley, 2005;Jamieson et al, 2012). The last of these is probably the most significant mechanism; when ice flows through a channel, drag can be generated by the side walls of the channel.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, observations suggest that recent increases in the temperature of water around Antarctica may have already triggered a process that will lead to the collapse of the Pine Island and Thwaites glaciers (Favier et al, 2014;Joughin et al, 2014). Unless an ice stream has exceptionally strong lateral buttressing (Robel et al, 2016), a marine ice sheet instability, once started, may only be stopped by modifying bathymetry to provide extra buttressing, as simulated by flow-band modeling on Thwaites Glacier (Wolovick and Moore, 2018). However, initial results from the BISICLES model evaluating the response of an idealized vulnerable marine glacier to imposed warming found that returning the entire water column to cooler conditions reversed the retreat that had begun during the warming (Asay-Davis et al, 2016).…”
Section: Ice Shelf Collapse and Dynamic Mass Lossmentioning
confidence: 99%